Phenylacetic Acid Is ISR Determinant Produced by Bacillus fortis IAGS162, Which Involves Extensive Re-modulation in Metabolomics of Tomato to Protect against Fusarium Wilt - Akram, Waheed; Anjum, Tehmina; Ali, Basharat (Frontiers in Plant Science, 2016)
B. fortis IAGS162 has been previously shown to induce systemic resistance in tomato plants against Fusarium wilt disease. In the first phase of current study, the ISR determinant was isolated from extracellular metabolites of this bacterium. ISR bioassays combined with solvent extraction, column chromatography and GC/MS analysis proved that phenylacetic acid (PAA) was the potential ISR determinant that significantly ameliorated Fusarium wilt disease of tomato at concentrations of 0.1 and 1 mM. In the second phase, the biochemical basis of the induced systemic resistance (ISR) under influence of PAA was elucidated by performing non-targeted whole metabolomics through GC/MS analysis. Tomato plants were again treated with PAA and fungal pathogen in either combinations. Exposure to PAA and subsequent pathogen challenge extensively re-modulated tomato metabolic networks along with defense related pathways. In addition, various phenylpropanoid precursors were significantly up-regulated in treatments receiving PAA. This work suggests that ISR elicitor released from B. fortis IAGS162 contribute to resistance against fungal pathogens through dynamic reprogramming of plant pathways that are functionally correlated with defense responses.